Simulation of Medium Truck Frame Based on ANSYS - Xu, Chang (Transactions on Computer Science and Intelligent Systems Research, 2024)
The frame is the important part of the car, as the understructure of assemble. the important assembly and structure on the car are based on the frame, and fixed to corresponding position, such as, engine, transmission, steering system and cab and so on. Force situation of the frame is very complex, it supports various load from road and loading, a large proportion of vehicle performance lie on structure performance of the frame. Therefore, the frame must have adequate intensity assure its fatigue life, and adequate rigidity assure its requirement of assemble and use. The requirements of modern automobile development are not limited to traditional mechanical analysis methods. This paper takes the frame of a medium truck as the research object using the finite element analysis software ANSYS to carry on the static mechanics. In this paper, the three-dimensional model is made by SolidWorks as the carrier according to the parameters of a selected frame, and leading-in the ANSYS to carry on finite element analysis.